Pathological findings in a patient with Fabry disease who died after 2.5 years of enzyme replacement - Schiffmann, Raphael; Rapkiewicz, Amy; Abu-Asab, Mones; Ries, Markus; Askari, Hasan; Tsokos, Maria; Quezado, Martha (Virchows Archiv, 2006)
We describe the postmortem findings of a 47-year-old man with Fabry disease, an X-linked glycolipid storage disorder, who was on enzyme replacement therapy with recombinant α-galactosidase A for more than 2 years. The patient had widespread atherosclerotic coronary artery disease that culminated in a massive acute myocardial infarction. Atherosclerotic lesions were seen in the right and left coronary systems, aorta, and the basilar artery. Typical Fabry cardiomyopathy and glomerular nephropathy were found. With the exception of vascular endothelial cells, extensive glycolipid storage deposits were seen in all vascular and nonvascular cells and organ systems. We conclude that, at least in this patient, repeated infusions with α-galactosidase A over a prolonged period did not appreciably clear storage material in cells other than vascular endothelial cells. These findings also illustrate accelerated atherosclerosis in susceptible patients with Fabry disease.
First online: 29 November 2005
Gesehen am 15.05.2019